'Criteria and Indicators for Sustainable Forest Management'. Papers Presented at a IUFRO/CIFOR/FAO Conference 'Sustainable Fore 2001
DOI: 10.1079/9780851993928.0005
|View full text |Cite
|
Sign up to set email alerts
|

Application of criteria and indicators to support sustainable forest management: some key issues.

Abstract: This paper contains discussions on: (1) the background to the development of criteria and indicators (C&I); (2) sustainable forest management; (3) the benefits that could be derived from the application of C&I; (4) scale issues and the application of C&I at the lowest management unit level; (5) challenges in implementing C&I and the role of scientists; and (6) the key issues and actions needed to enhance indicator development for each criterion (socioeconomic values, productivity, health and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 0 publications
0
35
0
3
Order By: Relevance
“…Raison et al (1998) identified many approaches to the development of criteria and indicators (C & I) for sustainable forest management: the study of benefits that can be obtained from the use of C & I; investigation of the extent of problem of application of C & I at the lowest level of the control unit; the role of the scientists in the implementation of C & I is studied; the key issues and actions necessary to promote the development of indicators for each criterion (significance of socio-economic values, productivity, health and bioenergy, soil and water, maintaining the balance of carbon and biodiversity) are observed. Mendoza and Prabhu (2004) grounded the expediency to use the theory of fuzzy sets to evaluate the criteria and indicators of sustainable forest management.…”
Section: Theoretical Foundations Multicriteria Evaluationmentioning
confidence: 99%
“…Raison et al (1998) identified many approaches to the development of criteria and indicators (C & I) for sustainable forest management: the study of benefits that can be obtained from the use of C & I; investigation of the extent of problem of application of C & I at the lowest level of the control unit; the role of the scientists in the implementation of C & I is studied; the key issues and actions necessary to promote the development of indicators for each criterion (significance of socio-economic values, productivity, health and bioenergy, soil and water, maintaining the balance of carbon and biodiversity) are observed. Mendoza and Prabhu (2004) grounded the expediency to use the theory of fuzzy sets to evaluate the criteria and indicators of sustainable forest management.…”
Section: Theoretical Foundations Multicriteria Evaluationmentioning
confidence: 99%
“…In fact, many have argued that forest management cannot be sustainable if it is not adaptive [48][49][50][51].…”
Section: (4) Monitoringmentioning
confidence: 99%
“…Similarly, land-owners that deforest exotic forest must surrender carbon credits, making deforestation less cost-effective (Karpas and Kerr 2011). Protections exist for indigenous forest, with only 2% of native forest available for timber harvest (Raison et al 2001). Further complexity is included in the scheme based on the age of the forest (pre-1990 or post-1989), and a minimum of nine years required from replanting to harvest (Karpas and Kerr 2011).…”
Section: New Zealand's Emissions Trading Schemementioning
confidence: 99%